Return to work and cancer: Perspectives of occupational therapists. (8th March 2021) - Hatton, Rebecca; Wallis, Amy; Chew, Angela; Stanley, Mandy; Smith, Andrew
Abstract: Introduction: Progress in the early detection, diagnosis, and treatment of cancer has translated into more people in Australia living with and beyond cancer. Therefore, there is a larger number of people returning to work following cancer treatment while managing ongoing symptoms of cancer, and side effects of treatment. The purpose of this study was to explore the facilitators and barriers for return to work for someone with cancer, from the perspective of occupational therapists. Method: This study used a qualitative descriptive design. Participants were recruited via key contacts within the industry and relevant interest groups, and included eight occupational therapists with experience supporting someone with cancer to return to work. Data were collected in semi‐structured in‐depth Interviews which were audio recorded, transcribed verbatim, and analysed thematically. Findings: Two main themes were developed; expectations of the cancer experience versus reality, and vulnerability during return to work. Occupational therapists perceived that the person with cancer, employers, family members, co‐workers, and society underestimate the impact of ongoing cancer symptoms on return to work. Return to work was challenging as survivors face unexpected challenges due to ongoing fatigue, cognitive difficulties, or psychological factors. Fear of relapse, concerns regarding disclosure affecting how people with cancer are perceived at work, and worries of leaving the high levels of professional support during treatment, also affected return to work. Conclusion: Findings from this study may contribute to occupational therapists and people with cancer setting realistic expectations for the return to work experience. Furthermore, it may provide support for occupational therapists to work more effectively with their clients to facilitate a smoother transition back to work as a cancer survivor.